Workshop on new strategies and tools for the eHealth library organized by the Andalusian eHealth Library (Journal of EAHIL, 2016)
The Andalusian eHealth Library (Biblioteca Virtual del Sistema Sanitario Publico de Andalucia, BV-SSPA), was created in June 2006. The 42 librarians who already worked for the Health System were integrated within this new system. The annual library meeting has been held every year since then, and in 2013 the EAHIL workshop held in Stockholm was the model to follow.